Thermal Study of New Refractory Heat-Shielding Materials Based on Mineral Raw - А.H.Kuldashev; I.U.Madjidov; S.М.Djuraev (Research Parks Publishing LLC, 2022)
the authors of the article provide information on the thermal studies carried out to obtain new fire and heat-shielding compositions based on local raw materials, including the study of their properties.